“The Two Brothers”: Reconciling Perceptual-Cognitive and Statistical Models of Musical Evolution - Jan, Steven (Frontiers in Psychology, 2018)
Various criticisms have been levelled against memetics. Putting aside that which claims it is a "meaningless metaphor" (Gould, in Blackmore, 1999, p. 17), another is that it is not truly scientific. This critique maintains that any insights memetics might offer are largely qualitative and intuitive (humanistic), rather than quantitative and empirical (scientific). Put more formally, this critique hinges partly on the Popperian notion of falsifiability (Popper, 1959), in the sense that to be seen as scientific memetics must be falsifiable, and for this to occur it needs to be formalized so that falsifiability can be assessed experimentally in relation to its specific claims. While the "units, events and dynamics" of memetic evolution have indeed been abstractly theorized (Lynch, 1998), they have not been applied systematically to real corpora in music. Some researchers, convinced of the validity of cultural evolution in more than the metaphorical sense adopted by much musicology, but perhaps sceptical of some or all of the claims of memetics, have attempted corpus-analysis techniques of music drawn from molecular biology, and these have offered strong evidence in favour of system-level change over time (Savage, 2017). This article argues for a synthesis between such quantitative approaches to the study of music-cultural change and the theory of memetics as applied to music (Jan, 2007), in particular the latter's perceptual-cognitive elements. It argues that molecular-biology approaches, while illuminating, ignore the psychological realities of music-information grouping, the transmission of such groups with varying degrees of fidelity, their selection according to relative perceptual-cognitive salience, and the power of this Darwinian process to drive the systemic changes that statistical methodologies measure.